Students' expressive engagement with historical film's moving images in a Maltese secondary history classroom. Issue 2 (26th October 2018) - Cutajar, Alexander
Abstract : This paper arises from research into using historical film in a Maltese secondary history classroom vis-à-vis its impact on student motivation, engagement and historical understanding. The paper outlines and discusses indicators of students' affective and cognitive engagement when responding to and analysing historical film's moving images – that is, extracts from footage of twentieth- and twenty-first century historical events captured live on camera as shown on newsreels, broadcast on television or forming part of a historical documentary. Using a single-site study, data was collected from two cohorts of Year 11 students following the history option programme. Each cohort was taught for an academic year and moving images were used as sources in history lessons. Analysing students' discourse in whole-class dialogues to obtain evidence for student engagement, findings showed different indicators of students' expressive verbal engagement with moving images: asking questions, making spontaneous observations, inserting oneself, establishing associations, and peer interaction. Findings suggest that underlying students' expressive engagement were the visual and auditory appeal of moving images, and classroom talk. Features of classroom talk in which moving images were used were consistent with views of dialogic teaching. Based on this evidence, it is argued that moving images can be used as a tool for engaging students, through classroom talk in a dialogic context, in developing historical understanding. It is also suggested that there is potential for using students' verbal utterances when analysing moving images for assessing learning.